Accounting Information System Reporting the Use of School Operational Costs (Case Study: SDIT Daar Ilmi Waykanan) - Rclani Amara; Suaidah Suaidah (Universitas Teknokrat Indonesia, 2021)
Every school that operates always issues and records the use of operational costs. Operational costs are commercial costs incurred by companies/agencies to support or support the operating activities of companies/agencies. These expenditures usually use the existing cash funds in the company/institution with a relatively small nominal. Similar to the process of managing school operational activities in general, SDIT Daar Ilmi Waykanan has used computers and manual bookkeeping in managing all financial recording activities. The computer application used is Microsoft Excel. Even though they already use a computer, there are still very frequent calculation errors and difficulties in manual recording. Because reporting on the use of operational costs must be done every month the school also needs time in conducting reports. There are frequent loss of documents and miscalculations and very wasteful of books/papers.Therefore, as a solution to the problems above, the authors build a web-based reporting system for the use of school operational costs, so that recording and reporting can be timely and more efficient. The recording method used in the development of the accounting information system for reporting the use of operational costs is the Imprest method where monthly recording is carried out repeatedly with the same nominal and time period. The method in developing this system uses the Prototype method, the prototype method itself is a software development method that intermediaries between developers and potential users, also described as an early version of a detailed description of a system desired by potential users. The results of this study indicate that the accounting information system for reporting the use of operating costs is very helpful for the school. Documents in reporting have been developed by adding several types of documents including general journals, cash receipts journals, cash disbursements journals and ledgers. This system can also generate reports of all incoming and outgoing funds.